ANALYZING INTENTIONAL PATINATION ON INDIAN SCULPTURES IN THE CONTEXT OF AGE, IMPERFECTION AND MATERIAL HIERARCHY: English - Chawla, Aashu; Sharma, Giriraj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
A layer of patina gets acquired over surfaces with the passage of time and usage. The ever-expanding definition of patina has been discussed in fields like chemistry, philosophy and aesthetics. Intentional patina is a process employed by sculptors to alter the surface of their artworks artificially without the risk of material damage. This paper aims to take a deep dive into explaining the fascination around patina. It discusses various aspects of aging, decaying, wear and tear, and alteration of visuals to explain its aesthetics. The paper takes post-modern and contemporary Indian sculptures as examples to illustrate its findings. It was found that intentional patina can undoubtedly add the context of time and environment the art was presumably exposed to. Variation in opacity, color, and texture of the patina can be used to celebrate imperfections and textures on the surface. There is also a break in the material hierarchy, choosing emotional attachment to a material over newer, polished finishes.